Stagewise water requirement of vegetable crops under protected and unprotected cultivation - SAGAR, ATISH; SINGH, P K (The Indian Journal of Agricultural Sciences, 2022)
The study was undertaken with the objective to estimate the crop water requirement of capsicum (Capsicum annuum L.), cucumber (Cucumis sativus L.) and tomato (Solanum lycopersicum L.) grown under naturally ventilated polyhouse and open environment during 2015–17 at Irrigation & Drainage Engineering, GBPUAT, Pantnagar. The water requirement was estimated using reference evapotranspiration and crop coefficient by incorporating the wetting percentage, crop coefficient and crop spacing. The water requirement was estimated for crops of two seasons grown under polyhouse and open environment and was found to be 203.77 mm and 101.68 mm for capsicum 1, 126.65 mm and 285.11 mm for capsicum 2, whereas 106.53 mm and 253.22 mm for cucumber 1, 130 mm and 605.8 mm for cucumber 2 respectively. During six months of growing period, the average water requirement for crops under polyhouse and open environment were found to be 30% higher than that of polyhouse.